THE IMPACT OF BANYUWANGI FESTIVAL TOWARDS TOURIST ENHANCEMENT TO BANYUWANGI CITY - Wardani, Galih Kusumo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Indonesiaâ€™s potential in developing the tourism industry is very promising,especially in Banyuwangi. The main purpose in this research is to analyze potential Banyuwangi trough BFEST (Banyuwangi Festival) that can effectively attract tourists to visit Banyuwangi as the main purpose of their first destination on vacation also make them back again after. The result showed that BFEST could significantly give impact to the visitor's decision making in choosing these potential tourism object including Red Island, Bangsring Underwater, and Ijen Crater as their destination. The conclusion is BFEST can give a good effect on SME in developing its business, so the potential of making the economic means will be wide open if managed properly supported with adequate advice. This can be used as land for absorbing employment and development of the quality of goods in the country, so in addition to the needs of souvenirs by tourists can be developed as the original export goods Banyuwangi.Â Keywords: BFEST, Banyuwangi, Tourism, SME, Red Island, Bangsring Underwater, Ijen Crater.